Composite hydroxypropyl methylcellulose skeleton sustained-release material and preparation method thereof

By constructing a three-dimensional network using a composite hydroxypropyl methylcellulose (HPMC) framework material, combined with sodium alginate and chitosan, and employing dual crosslinking and nanoemulsion dispersion technology, the release instability and initial burst release issues of the HPMC framework system were resolved. This resulted in stable and controllable drug release and colon-targeting effects, making it suitable for the field of sustained-release materials.

CN121338013APending Publication Date: 2026-01-16SHIJIAZHUANG VOCATIONAL TECH INST
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511674152.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-14
Publication Date
2026-01-16

AI Technical Summary

Technical Problem

The drug release behavior of existing HPMC framework systems is easily affected by the environment, and there are problems such as initial burst release effect, insufficient hardness and release delay. In addition, traditional blending or chemical modification methods are complex and costly.

Method used

The composite hydroxypropyl methylcellulose backbone material is used, and a three-dimensional network structure is constructed by sodium alginate and chitosan. The release rate is adjusted by combining hydrophobic barrier agents and pore-forming agents. A dual cross-linking strategy is used to enhance the backbone stability. Enzyme-sensitive excipients are added to achieve colon-targeted release. At the same time, the active ingredients are loaded by nanoemulsion dispersion technology.

Benefits of technology

It achieves stable and controllable drug release, avoids burst release, enhances the structural integrity of the material and colon-targeting effect, is suitable for chronic disease patients who need long-term nutritional supplementation, and the material is safe and biodegradable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121338013A_ABST
    Figure CN121338013A_ABST
Patent Text Reader

Abstract

The invention relates to a composite hydroxypropyl methylcellulose skeleton sustained-release material and a preparation method thereof, and belongs to the technical field of drug sustained release. The sustained-release material is prepared from 70 to 90 parts of hydroxypropyl methylcellulose (HPMC), 10 to 20 parts of sodium alginate, 8 to 15 parts of chitosan, 0.1 to 0.2 part of Omega-3 fatty acid, 0.05 to 0.06 part of vitamin D, 2.5 to 5 parts of soluble calcium salt-zinc salt composite cross-linking agent, 0.5 to 1.5 parts of hydrolyzable cross-linking agent, 3 to 10 parts of enzyme sensitive auxiliary material, 1 to 5 parts of pore-foaming agent and 2 to 8 parts of hydrophobic blocking agent. The preparation method comprises the steps of raw material pretreatment and dry mixing, active component dispersion liquid preparation, wet granulation and primary cross-linking, secondary cross-linking and drying, vacuum drying and size stabilization, curing and packaging and the like. The sustained-release material provided by the invention has the advantages of controllable drug release rate, good mechanical strength and biodegradability, is suitable for sustained-release delivery of Omega-3 fatty acid, vitamin D and other active components, and can improve the bioavailability and stability of drugs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of pharmaceutical formulation technology, specifically to a composite hydroxypropyl methylcellulose (HPMC) matrix sustained-release material and its preparation method. Background Technology

[0002] Hydroxypropyl methylcellulose (HPMC) is a nonionic cellulose ether and one of the most commonly used and important sustained-release materials for preparing hydrophilic gel matrix tablets. Its sustained-release principle lies in the rapid hydration of its surface upon contact with water to form a gel layer. This gel layer acts as a barrier, controlling the inward permeation of water and the outward diffusion of the drug, thereby achieving the slow release of the drug.

[0003] However, single HPMC framework systems also have some inherent drawbacks: release behavior is easily affected by the environment, and the drug release rate may be affected by factors such as gastrointestinal pH, enzymes, and hydrodynamic conditions, resulting in poor correlation between in vivo and in vitro release behavior; for drugs with high water solubility, a burst release effect of the initial dose is likely to occur before the gel layer is fully established; high HPMC content may lead to insufficient tablet hardness, making them prone to wear and breakage during packaging and transportation; some HPMC grades have a slower hydration rate, which may lead to a delayed initiation of drug release.

[0004] To overcome the aforementioned drawbacks, existing technologies typically employ methods such as blending multiple polymer materials or chemical modification. However, simple physical blending may result in poor compatibility, while chemical modification processes are complex and costly. Therefore, developing a composite HPMC sustained-release material that is simple to process, exhibits excellent performance, and provides stable and controllable release is of great significance. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a composite hydroxypropyl methylcellulose backbone sustained-release material. Another purpose of this invention is to provide a method for preparing the above-mentioned composite sustained-release material.

[0006] Technical solution: A composite hydroxypropyl methylcellulose (HPMC) backbone sustained-release material, comprising the following components by weight: 70-90 parts of hydroxypropyl methylcellulose (HPMC), 10-20 parts of sodium alginate, 8-15 parts of chitosan, 0.1-0.2 parts of Omega-3 fatty acid, 0.05-0.06 parts of vitamin D, 2.5-5 parts of soluble calcium-zinc salt composite crosslinking agent, 0.5-1.5 parts of hydrolyzable crosslinking agent, 3-10 parts of enzyme-sensitive excipient, 1-5 parts of pore-forming agent, and 2-8 parts of hydrophobic barrier agent; the parts are the dry weight of each component.

[0007] Preferably, the soluble calcium salt-zinc salt composite crosslinking agent is a mixture of calcium pantothenate and zinc citrate, with a weight ratio of calcium pantothenate:zinc citrate = 4:1.

[0008] Preferably, the hydrolyzable crosslinking agent is either bis(vinyl sulfone) polyethylene glycol or glutaraldehyde.

[0009] Preferably, the enzyme-sensitive excipient is either pectin or guar gum.

[0010] Preferably, the pore-forming agent is a mixture of glycine and sodium bicarbonate, wherein the weight ratio of glycine to sodium bicarbonate is 1:3.

[0011] Preferably, the hydrophobic barrier is beeswax-composite magnesium stearate, wherein the preparation method of beeswax-composite magnesium stearate is as follows: Beeswax and magnesium stearate are accurately weighed according to a weight ratio of beeswax:magnesium stearate = 4:1. Dichloromethane, weighing 25 times the weight of beeswax, is added. The mixture is stirred at 300-500 rpm at room temperature until the solid is completely dissolved and the solution is clear and transparent. Deionized water, weighing 50 times the weight of beeswax, is added, along with PVA powder, weighing 0.5 times the weight of beeswax. The powder is slowly sprinkled onto the water surface while stirring at 500-800 rpm. After swelling for 15-30 minutes, the mixture is heated to 80-90°C and stirred at 600-800 rpm for 1 hour until the PVA is completely dissolved. The mixture is then cooled to room temperature. The aqueous phase is placed under a high-speed shear mill, and the mill speed is adjusted to 10000 rpm. At 10,000 rpm, the dichloromethane phase was slowly and uniformly added dropwise to the center of the aqueous phase under high-speed stirring. After the addition was complete, the mixture was sheared and emulsified at 10,000 rpm for 10 minutes to form a milky white "coarse emulsion". The coarse emulsion was transferred to a suitable ultrasonic container, with a power of 400 W, a working time of 5 seconds, an interval of 5 seconds, and a total ultrasonic treatment time of 3 minutes. After treatment, a finer and more stable O / W type emulsion was obtained. The emulsified emulsion was placed at 35 ℃ and continuously evaporated under reduced pressure for 6 hours to ensure that the dichloromethane was completely removed. After the solvent was evaporated, the mixture was filtered and the surface of the filter cake was rinsed three times with pre-cooled deionized water at about 4 ℃, each time with a weight of about 10 times the weight of beeswax. The mixture was then vacuum dried at 28 ℃ with a vacuum degree of -0.09 MPa or higher until constant weight was achieved. The sample was then passed through a 100-mesh sieve to obtain a loose and fine white beeswax-magnesium stearate composite powder.

[0012] Preferably, the HPMC has a viscosity grade of 100 mPa·s to 100,000 mPa·s.

[0013] A method for preparing a composite hydroxypropyl methylcellulose backbone sustained-release material includes the following steps: S1. Raw material pretreatment and dry mixing: Pass the specified amounts of hydroxypropyl methylcellulose (HPMC), sodium alginate, chitosan, enzyme-sensitive excipients, pore-forming agents and hydrophobic barrier agents through an 80-mesh sieve to ensure uniform particle size. Then, place these dried powder components in a three-dimensional mixer and mix at a speed of 20-30 rpm for 15-30 minutes to obtain a uniform dry mixture A. S2. Preparation of active ingredient dispersion: Omega-3 fatty acids and beeswax-composite magnesium stearate, accounting for 1 / 3 of the total hydrophobic hindrance, are melt-mixed at 65±5℃ to form an oil phase. Simultaneously, vitamin D is dissolved in anhydrous ethanol at 10-15 times its weight to obtain a vitamin D ethanol solution. A 0.1%-0.5% (w / v) poloxamer 188 aqueous solution is prepared as the aqueous phase. Under high-speed shearing at 8000±2000 rpm, the oil phase is slowly added to the aqueous phase at a rate of 1-3% (v / v, volume percentage of the aqueous phase) per minute to form a primary emulsion. Subsequently, under mechanical stirring at 400-600 rpm, the vitamin D ethanol solution is uniformly added to the above emulsion within 1-2 minutes. After stirring for 10 minutes, the mixture is homogenized for 3-5 cycles under a high-pressure homogenizer at a pressure of 50-100 MPa to obtain active ingredient nanoemulsion dispersion B. S3. Transfer the dry mixture A obtained in step S1 to a high-speed shear granulator and start it with low-speed stirring (blade speed 100-300 rpm). Use a peristaltic pump to spray the dispersion B obtained in step S2 as a binder at a rate of 5-15 mL / kg per minute relative to the weight of the dry mixture A. After granulation, dissolve the soluble calcium salt-zinc salt composite crosslinking agent in 20-30 times its weight of purified water to make a crosslinking agent solution. While maintaining the blade speed at 50-150 rpm, slowly add the crosslinking agent solution to the wet material at a rate of 3-8 mL / kg per minute relative to the weight of the wet material. After the addition is complete, continue the crosslinking reaction for 15±5 minutes to make a soft material that "can be formed into a ball when squeezed by hand and disperses easily when pressed". S4. Secondary crosslinking and drying: The wet particles obtained in step S3 are granulated by passing them through a 20-mesh sieve using a swing granulator. Then, they are dispersed in a dilute solution of a hydrolyzable crosslinking agent with a concentration of 0.5%-1%. The mixture is slowly stirred at room temperature to carry out secondary crosslinking and curing for 1-2 hours. After the crosslinking is completed, the particles are filtered and collected. S5. Vacuum drying and granulation: The cross-linked wet particles are placed in a vacuum drying oven and dried under vacuum conditions of 40-50 ℃ and -0.08 to -0.1 MPa until the moisture content is less than 5%. The dried particles are then lightly crushed by a universal pulverizer and granulated through a 30-mesh sieve to obtain uniform particles with good flowability. S6. Curing and Packaging: The granulated sustained-release material particles are placed in a constant temperature and humidity room at 25±2 ℃ and 40%±5% for 24 hours to cure. Finally, they are sealed in aluminum foil bags to obtain the composite hydroxypropyl methylcellulose skeleton sustained-release material.

[0014] The beneficial effects of this invention are as follows: 1. A robust three-dimensional network structure was constructed using hydroxypropyl methylcellulose (HPMC) as the main framework, combined with the synergistic gel-forming ability of sodium alginate and chitosan, which significantly prolongs the drug release time. The addition of a hydrophobic barrier (beeswax-magnesium stearate complex) and a pore-forming agent (glycine-sodium bicarbonate mixture) dually regulates the release rate: the hydrophobic component slows down water penetration, and the pore-forming agent forms microporous channels during dissolution, achieving linear or constant-rate release and avoiding burst release.

[0015] 2. A dual crosslinking strategy is adopted. The first crosslinking uses a soluble calcium-zinc salt composite crosslinking agent (calcium pantothenate-zinc citrate) to strengthen the skeleton through ionic bonds. The second crosslinking uses a hydrolyzable crosslinking agent (bis(vinyl sulfone) polyethylene glycol) to form a covalent network, making the skeleton resistant to gastrointestinal fluid erosion and maintaining structural integrity. The crosslinking process is optimized (wet granulation and solution crosslinking) to ensure uniform crosslinking and improve the stability of the material in long-term storage or harsh environments.

[0016] 3. Add enzyme-sensitive excipients (such as pectin or guar gum). These materials are degraded by specific enzymes in the colon, thereby achieving targeted release in the colon, increasing local drug concentration, and reducing systemic side effects. This feature is suitable for the treatment of intestinal diseases or targeted nutritional supplementation, enhancing the therapeutic effect.

[0017] 4. Achieving integrated nutritional function, directly loading active nutrients such as Omega-3 fatty acids and vitamin D, providing nutritional support simultaneously during the slow-release process, especially suitable for patients with chronic diseases who need long-term nutritional supplementation. Through nanoemulsion dispersion technology (step S2), the stability and bioavailability of fat-soluble components are improved.

[0018] 5. The preparation method adopts a process of dry mixing-wet granulation-secondary cross-linking-vacuum drying to ensure uniform dispersion of components, sufficient cross-linking, and high batch-to-batch consistency; the curing step (constant temperature and humidity treatment) releases the internal stress of the material and further stabilizes the sustained-release performance; the composite preparation process of the hydrophobic barrier (emulsification of beeswax and magnesium stearate-solvent evaporation method) obtains micro-uniform powder, which enhances the hydrophobic effect and avoids agglomeration.

[0019] 6. The main components (HPMC, sodium alginate, chitosan, etc.) are natural or pharmaceutical grade polymers with no toxic side effects; the crosslinking agent and pore-forming agent are used in precise amounts, meeting pharmaceutical standards; the material is biodegradable or excreted in the body, ensuring high safety. Attached Figure Description

[0020] Figure 1 The particle size distribution diagram of the composite hydroxypropyl methylcellulose backbone sustained-release material prepared for this invention.

[0021] Figure 2The image shows a comparison of the sustained-release curves of piribedil sustained-release tablets prepared by compressing the composite hydroxypropyl methylcellulose matrix sustained-release material and hydroxypropyl methylcellulose prepared by the present invention, as well as the tablets prepared by compressing the composite hydroxypropyl methylcellulose matrix sustained-release material without the addition of hydrophobic blocking agents, in simulated gastric fluid.

[0022] Figure 3 Water contact angle diagram of beeswax composite magnesium stearate and pure hydroxypropyl methylcellulose prepared according to the present invention.

[0023] Figure 4 A comparison of the sustained-release curves of aspirin sustained-release tablets prepared from the composite hydroxypropyl methylcellulose matrix sustained-release material and pure hydroxypropyl methylcellulose tablets in simulated colonic fluid containing pectinase, as presented in this invention. Detailed Implementation

[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] Example 1: Formula (by dry weight): Hydroxypropyl methylcellulose (HPMC, viscosity 4000 mPa·s): 70 parts; Sodium alginate: 10 parts; Chitosan: 8 parts; Omega-3 fatty acids: 0.1 part; Vitamin D: 0.05 parts; Soluble calcium salt-zinc salt composite crosslinking agent (calcium pantothenate: zinc citrate = 4:1): 2.5 parts, of which 2.0 parts are calcium pantothenate and 0.5 parts are zinc citrate; Hydrolyzable crosslinking agent (bis(vinyl sulfone) polyethylene glycol): 0.5 parts; Enzyme-sensitive excipient (pectin): 3 parts; Pore-forming agent (glycine:sodium bicarbonate = 1:3): 1 part, of which glycine is 0.25 parts and sodium bicarbonate is 0.75 parts; Hydrophobic barrier (beeswax-based magnesium stearate): 2 parts. According to the preparation method, this 2-part composite powder is prepared from 1.6 parts beeswax and 0.4 parts magnesium stearate. Its water contact angle diagram is attached. Figure 3 .

[0026] Preparation method: S1. Raw material pretreatment and dry mixing: HPMC, sodium alginate, chitosan, pectin, glycine-sodium bicarbonate mixture, and beeswax-compound magnesium stearate are each passed through an 80-mesh sieve. The sieved dry powders are placed in a three-dimensional mixer and mixed at 25 rpm for 20 minutes to obtain a uniform dry mixture A.

[0027] S2. Preparation of active ingredient dispersion: Take 0.1 parts of Omega-3 fatty acid and 1 / 3 of the total amount of beeswax composite magnesium stearate, melt and mix at 65 ℃ to form an oil phase. At the same time, dissolve 0.05 parts of vitamin D in an appropriate amount of anhydrous ethanol. Under high-speed shearing at 8000 rpm, slowly add the oil phase to an aqueous solution containing emulsifier poloxamer 188 to form a primary emulsion. Then, add the ethanol solution of vitamin D to the emulsion under stirring. After homogenization, obtain active ingredient nanoemulsion dispersion B.

[0028] S3. Wet granulation and primary crosslinking: Transfer the dry mixture A to a high-speed shear granulator. While stirring, slowly spray the dispersion B as a binder for granulation. Then, dissolve 2.5 parts of soluble calcium salt-zinc salt composite crosslinking agent in an appropriate amount of purified water and slowly add it to the wet material under low-speed shearing. The crosslinking reaction takes 15 minutes to produce a suitable soft material.

[0029] S4. Secondary crosslinking and drying: The wet granules are granulated by passing them through a 20-mesh sieve using a swing granulator, and then dispersed in a 0.8% dilute solution of bis(vinyl sulfone) polyethylene glycol. The mixture is slowly stirred at room temperature to carry out secondary crosslinking and curing for 1.5 hours. After the crosslinking is completed, the granules are filtered and collected.

[0030] S5. Vacuum drying and granulation: The cross-linked wet particles are placed in a vacuum drying oven and dried at 45 ℃ and -0.09 MPa until the moisture content is less than 5%. The dried particles are then lightly crushed by a universal pulverizer and granulated through a 30-mesh sieve to obtain uniform particles with good flowability.

[0031] S6. Maturation and Packaging: The granulated particles are placed in a constant temperature and humidity chamber at 25±2 ℃ and 40%±5% for 24 hours for maturation. Finally, they are sealed in aluminum foil bags to obtain the composite hydroxypropyl methylcellulose backbone sustained-release material. The particle size distribution diagram is attached. Figure 1 .

[0032] Example 2: Formula (by dry weight): Hydroxypropyl methylcellulose (HPMC, viscosity 100,000 mPa·s): 90 parts; Sodium alginate: 20 parts; Chitosan: 15 parts; Omega-3 fatty acids: 0.2 parts; Vitamin D: 0.06 parts; Soluble calcium salt-zinc salt composite crosslinking agent (calcium pantothenate: zinc citrate = 4:1): 5 parts, of which 4.0 parts are calcium pantothenate and 1.0 part is zinc citrate; Hydrolyzable crosslinking agent (glutaraldehyde): 1.5 parts Enzyme-sensitive excipient (guar gum): 10 parts Pore-forming agent (glycine:sodium bicarbonate = 1:3): 5 parts, of which 1.25 parts are glycine and 3.75 parts are sodium bicarbonate; Hydrophobic barrier (beeswax composite magnesium stearate): 8 parts. According to the preparation method, this 8-part composite powder is prepared from 6.4 parts beeswax and 1.6 parts magnesium stearate.

[0033] Preparation method: S1, Same as Example 1, but the mixing speed is 30 rpm and the time is 30 minutes.

[0034] S2. Take 0.2 parts of Omega-3 fatty acid and 1 / 3 of the total amount of hydrophobic retardant beeswax composite magnesium stearate, melt mix them at 70℃, dissolve 0.06 parts of vitamin D in ethanol, and prepare nanoemulsion dispersion B under high-speed shearing at 10000 rpm.

[0035] S3. After granulation using dispersion B, crosslinking is performed once using 5 parts of calcium-zinc composite crosslinking agent solution for 20 minutes.

[0036] S4. After passing through a 20-mesh sieve, disperse in a 1% dilute glutaraldehyde solution and undergo secondary cross-linking and curing for 2 hours.

[0037] S5. Vacuum dry at 50 ℃ and -0.1 MPa until the moisture content is qualified, and then granulate.

[0038] S6. Same as in Example 1, packaged after ripening.

[0039] Example 3: Formula (by dry weight): Hydroxypropyl methylcellulose (HPMC, viscosity 15,000 mPa·s): 80 parts; Sodium alginate: 15 parts; Chitosan: 12 parts; Omega-3 fatty acids: 0.15 parts; Vitamin D: 0.055 parts; Soluble calcium salt-zinc salt composite crosslinking agent (calcium pantothenate: zinc citrate = 4:1): 3.75 parts, of which 3.0 parts are calcium pantothenate and 0.75 parts are zinc citrate; Hydrolyzable crosslinking agent (bis(vinyl sulfone) polyethylene glycol): 1.0 part; Enzyme-sensitive excipient (pectin): 6.5 parts; Pore-forming agent (glycine:sodium bicarbonate = 1:3): 3 parts, of which glycine is 0.75 parts and sodium bicarbonate is 2.25 parts; Hydrophobic barrier (beeswax composite magnesium stearate): 5 parts. According to the preparation method, this 5-part composite powder is prepared from 4.0 parts beeswax and 1.0 parts magnesium stearate.

[0040] Preparation method: S1. Same as Example 1, mixing speed is 20 rpm, time is 15 minutes.

[0041] S2. Take 0.15 parts of Omega-3 fatty acid and 1 / 3 of the total amount of hydrophobic retardant beeswax composite magnesium stearate, melt mix them at 60 ℃, dissolve 0.055 parts of vitamin D in ethanol, and prepare nanoemulsion dispersion B under high-speed shearing at 5000 rpm.

[0042] S3. After granulation using dispersion B, perform cross-linking once with 3.75 parts of calcium-zinc composite cross-linking agent solution for 10 minutes.

[0043] S4. After passing through a 20-mesh sieve, disperse in a 0.5% dilute solution of bis(vinyl sulfone) polyethylene glycol and perform secondary cross-linking and curing for 1 hour.

[0044] S5. Vacuum dry at 40 ℃ and -0.08 MPa until the moisture content is qualified, and then granulate.

[0045] S6. Same as in Example 1, packaged after ripening.

[0046] Comparative Example 1: Same as Example 3, except that no enzyme-sensitive excipient (pectin) is added.

[0047] Comparative Example 2: Same as Example 3, except that the secondary crosslinking step (S4) is omitted. After the first crosslinking in step S3, drying (S5) and aging (S6) are performed directly.

[0048] Comparative Example 3: Same as Example 3, except that no hydrophobic barrier agent (beeswax composite magnesium stearate) is added. In step S2, only the active ingredient is made into a nanoemulsion, without adding 1 / 3 of the hydrophobic barrier agent.

[0049] Comparative Example 4: Same as Example 3, except that the pore-forming agent (glycine-sodium bicarbonate mixture) is replaced with an equal amount of water-insoluble and gas-free microcrystalline cellulose.

[0050] Comparative Example 5: Formula: Same as Example 3.

[0051] Preparation method: The traditional single-step wet granulation method is adopted, in which all powder components (including two crosslinking agents) in S1 are mixed at one time, and then pure water (instead of dispersion B) is used as a binder for granulation, omitting the nanoemulsion dispersion of active ingredients (S2) and the stepwise crosslinking process.

[0052] The statistical results of the experiment are shown in the table below:

[0053] Note: Comparative examples 2 and 3 were almost completely released 12 hours ago.

[0054] Experimental results: All three examples exhibited stable and linear release characteristics (R0). 2 >0.98), and no burst release; Comparative Example 3 (without hydrophobic blocker) showed severe burst release and excessively rapid release, demonstrating the necessity of the hydrophobic blocker. The comparison of the sustained-release curves in simulated gastric juice is shown in the appendix. Figure 2 Comparative Example 2 (without secondary cross-linking) exhibited poor skeleton strength, rapid dissolution, and burst release, demonstrating the crucial role of dual cross-linking in structural integrity. Examples 1-3 showed significantly accelerated release rates (release increment >30%) upon contact with colonic enzymes, while Comparative Example 1 (without enzyme-sensitive excipients) showed no such response and a smooth release curve, proving that enzyme-sensitive excipients are the core for achieving colon-targeted release (see Appendix). Figure 4 Although Comparative Example 4 (with a pore-forming agent) had a slower initial release, its release rate in the intestinal fluid environment after 6 hours was lower than that of Example 3, and the release was incomplete after 12 hours. This indicates that the glycine-sodium bicarbonate system has a unique effect on generating gas and forming pores at a specific pH, which is superior to ordinary fillers. Comparative Example 5 (conventional process) performed the worst in almost all indicators, with poor release uniformity (high burst release), uneven distribution of active ingredients (high RSD), and poor storage stability. This strongly proves that the nanoemulsion dispersion technology and stepwise crosslinking preparation process described in this invention are crucial for achieving "integrated nutritional function" and "high batch-to-batch consistency".

[0055] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.

Claims

1. A composite hydroxypropyl methylcellulose matrix sustained release material characterized in that, The hydroxypropyl methyl cellulose (HPMC) 70-90 parts by weight, sodium alginate 10-20 parts by weight, chitosan 8-15 parts by weight, Omega-3 fatty acid 0.1-0.2 parts by weight, vitamin D 0.05-0.06 parts by weight, soluble calcium-zinc salt complex crosslinking agent 2.5-5 parts by weight, hydrolyzable crosslinking agent 0.5-1.5 parts by weight, enzyme-sensitive auxiliary material 3-10 parts by weight, pore-forming agent 1-5 parts by weight, hydrophobic blocking agent 2-8 parts by weight; the fraction is the fraction of the dry weight of each component.

2. The composite hydroxypropyl methylcellulose matrix sustained release material according to claim 1, wherein The soluble calcium-zinc salt complex crosslinking agent is a mixture of calcium pantothenate and zinc citrate, and the weight ratio of calcium pantothenate to zinc citrate is 4:

1.

3. The composite hydroxypropyl methylcellulose matrix sustained release material according to claim 1, wherein The hydrolyzable crosslinking agent is any one of bis (vinyl sulfone) polyethylene glycol or glutaraldehyde.

4. The composite hydroxypropyl methylcellulose matrix sustained release material according to claim 1, wherein The enzyme-sensitive auxiliary material is any one of pectin or guar gum.

5. The composite hydroxypropyl methylcellulose matrix sustained release material according to claim 1, wherein The pore-forming agent is a mixture of glycine and sodium bicarbonate, and the weight ratio of glycine to sodium bicarbonate is 1:

3.

6. The composite hydroxypropyl methylcellulose matrix sustained release material according to claim 1, wherein The hydrophobic blocking agent is a mixture of beeswax and magnesium stearate, and the preparation method of the mixture is as follows: the weight ratio of beeswax to magnesium stearate is 4:1, the beeswax and magnesium stearate are accurately weighed, dichloromethane with a weight of 25 times the weight of the beeswax is added, stirring at 300-500 rpm at room temperature until the solid is completely dissolved, the solution is clear and transparent, and the solution is ready for use; deionized water with a weight of 50 times the weight of the beeswax is measured, PVA powder with a weight of 0.5 times the weight of the beeswax is added, and the water surface is slowly poured into the water under stirring at 500-800 rpm, and after swelling for 15-30 minutes, heating to 80-90°C and stirring at 600-800 rpm for 1 hour until the PVA is completely dissolved, and then cooling to room temperature for use; the above water phase is placed in a high-speed shearing machine, the shearing machine is started, the speed is adjusted to 10000 rpm, the dichloromethane phase above is slowly and uniformly added to the center of the high-speed stirring water phase, after the addition is completed, the speed is kept at 10000 rpm for 10 minutes, a "coarse emulsion" of milky white color is formed, the coarse emulsion is transferred to a container suitable for ultrasonic treatment, the power is 400 W, the working time is 5 seconds, the intermittent time is 5 seconds, and the total ultrasonic treatment time is 3 minutes, and a more delicate and stable O / W emulsion is obtained; the emulsified emulsion is placed at 35°C and continuously evaporated under reduced pressure for 6 hours to ensure that the dichloromethane is completely removed; after the solvent evaporation is completed, the filter cake surface is washed 3 times with pre-cooled deionized water at about 4°C, each time with a weight of about 10 times the weight of the beeswax, and then vacuum dried at 28°C, the vacuum degree is above -0.09 MPa, until the constant weight, the sample is sieved through a 100 mesh sieve, and a loose and delicate white beeswax-magnesium stearate composite powder is obtained.

7. The composite hydroxypropyl methylcellulose matrix sustained release material according to claim 1, wherein The viscosity grade of the HPMC is 100 mPa·s to 100,000 mPa·s.

8. A process for the preparation of a composite hydroxypropyl methylcellulose matrix sustained release material as claimed in any one of claims 1 to 7, characterized in that, The method comprises the following steps: S1, raw material pretreatment and dry mixing: a predetermined amount of hydroxypropyl methylcellulose (HPMC), sodium alginate, chitosan, enzyme-sensitive excipients, pore-forming agents and hydrophobic retardants were respectively passed through an 80-mesh sieve to ensure uniform particles, and then the dry powder components were placed in a three-dimensional mixer and mixed at a speed of 20-30 rpm for 15-30 minutes to obtain a uniform dry mixture A; S2, preparation of active ingredient dispersion: Omega-3 fatty acids were mixed with 1 / 3 of the total weight of hydrophobic retardants to form an oil phase, while vitamin D was dissolved in 10-15 times its weight of anhydrous ethanol to obtain a vitamin D ethanol solution, and a 0.1%-0.5%(w / v) poloxamer 188 aqueous solution was prepared as the water phase, under high-speed shearing at 8000±2000 rpm, the oil phase was slowly added to the water phase at a rate of 1-3% (v / v) per minute to form a colostrum, then the vitamin D ethanol solution was added to the above emulsion at a constant speed for 1-2 minutes under mechanical stirring at 400-600 rpm, and after 10 minutes of continuous stirring, the active ingredient nanoemulsion dispersion B was obtained by homogenizing 3-5 cycles at a pressure of 50-100 MPa using a high-pressure homogenizer; S3, the dry mixture A obtained in step S1 was transferred to a high-speed shearing granulator, and the dispersion B prepared in step S2 was sprayed as a binder at a rate of 5-15 mL / kg per minute based on the weight of the dry mixture A, after granulation, the soluble calcium-zinc complex crosslinking agent was dissolved in 20-30 times its weight of purified water to prepare a crosslinking agent solution, and the crosslinking agent solution was slowly added to the wet material at a rate of 3-8 mL / kg per minute based on the weight of the wet material while maintaining the paddle speed at 50-150 rpm, after addition, the crosslinking reaction was continued for 15±5 minutes to produce a soft material that can be held together and dispersed by light pressure; S4, secondary crosslinking and drying: the wet granules obtained in step S3 were sieved through a 20-mesh sieve using a swing granulator, then dispersed in a 0.5%-1% dilute solution of the hydrolyzable crosslinking agent, and slowly stirred at room temperature for 1-2 hours for secondary crosslinking and solidification, after crosslinking, the granules were collected by filtration; S5, vacuum drying and sizing: the crosslinked wet granules were placed in a vacuum drying oven and dried at 40-50 ℃ under vacuum conditions of -0.08 to -0.1 MPa to a moisture content of less than 5%, the dried granules were slightly crushed using a universal crusher and then sieved through a 30-mesh sieve for sizing to obtain uniform granules with good flowability; S6, maturation and packaging: the sized sustained-release material granules were placed in a constant temperature and humidity chamber at a temperature of 25±2 ℃ and a humidity of 40%±5% for maturation for 24 hours, finally, the aluminum foil bag was sealed for packaging, and the composite hydroxypropyl methylcellulose matrix sustained-release material was obtained.

Citation Information

Cited By

  • Sustained-release tablet type aspirin medicine and preparation method thereof

    CN121668118A

  • A low-density small-particle-size hydroxypropyl methylcellulose for sustained-release matrix and a preparation method thereof

    CN122520816A